Consumers' perceived post purchase risk in luxury services. (February 2017) - Chang, Yonghwan; Ko, Yong Jae
Abstract: The objectives of this study are to: (1) define the concept of perceived post purchase (3P) luxury risk and (2) develop and validate a psychometrically sound 3P Luxury Risk Scale. A qualitative study and two field studies were conducted to develop and test the scale, and to examine the predictive validity of 3P luxury risk in a nomological network of word-of-mouth (WOM). The survey data is gathered from 333 actual customers of five golf clubs. Integrating structural equation modeling with propensity score analysis, the results of Study 1 reveal that 12 items adequately capture the dimensions of 3P luxury risk. After controlling for framing effects, the results of Study 2 indicate that all of the dimensions of 3P luxury risk negatively influence WOM. This article attempts to shed a new light on the realm of luxury risk studies incorporating normative and behavioral decision-making approaches.